Clause of proper application prescribed in article 300 of the Polish Labour Code in relation to modi=cation of a provisions of the Polish Civil Code - Jaskulska, Jagoda (Studia Iuridica Toruniensia, 2017)
The article includes deliberations on the issue of proper application of provisions of the Polish Civil Code to matters relating to relationship of employment, which are not regulated by labour law provisions. Among numerous issues and doubts arising in relation to functions of Article 300 of the Polish Labour Code in the legal system, the author has distinguished significance of a reservation of proper application of the provisions for the purposes of the labour law and, in particular, in the context of admissible modification of provisions of the Polish Civil Code. The analysis of opinions of the doctrine and review of the case law of the Supreme Court have made it possible to formulate a critical opinion on the possibility to amend provisions of the Polish Civil Code in the progress of application of the same in connection with article 300 of the Polish Labour Code. The conclusions have been extended by indicated threats arising from modification of provisions applied after fulBlment of prerequisites of article 300 of the Polish Labour Code as well as several trends of modifications, which would aim at limitation or elimination of any doubts and divergences as regards interpretation.